2017
DOI: 10.1007/s00264-017-3465-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analgaesia with lumbar epidurals and lumbar plexus nerve blocks in patients receiving multimodal analgaesics following primary total hip arthroplasty: a retrospective analysis

Abstract: Following primary total hip arthroplasty, lumbar plexus nerve blocks provide effective post-operative analgaesia with decreased opiate consumption compared with lumbar epidural catheters. Lumbar plexus blocks also promote earlier post-operative ambulation and are compatible with post-operative prophylactic anticoagulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…All opioids were converted to intravenous morphine milligram equivalents (MME) for comparison (1 mg morphine intravenous equal to fentanyl 10 µg intravenous, hydromorphone 0.15 mg intravenous, oxycodone 2 mg oral, and meperidine 7.5 mg intravenous) 3. A previous study found mean intravenous MME in patients undergoing THA with a LPB was 20.4±13.1 MME at 24 hours 2. A prior power calculation found a sample size of 92 subjects per group (184 total) would provide 80% power to detect non-inferiority using a one-sided two-sample t-test (significance level α=0.05) and assuming a mean of 20.4±13.1 MME in the LPB group, the margin of equivalence is 20% of the mean opioid consumption in the QL group, and a true difference between the means equals 0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All opioids were converted to intravenous morphine milligram equivalents (MME) for comparison (1 mg morphine intravenous equal to fentanyl 10 µg intravenous, hydromorphone 0.15 mg intravenous, oxycodone 2 mg oral, and meperidine 7.5 mg intravenous) 3. A previous study found mean intravenous MME in patients undergoing THA with a LPB was 20.4±13.1 MME at 24 hours 2. A prior power calculation found a sample size of 92 subjects per group (184 total) would provide 80% power to detect non-inferiority using a one-sided two-sample t-test (significance level α=0.05) and assuming a mean of 20.4±13.1 MME in the LPB group, the margin of equivalence is 20% of the mean opioid consumption in the QL group, and a true difference between the means equals 0.…”
Section: Methodsmentioning
confidence: 99%
“…Total hip arthroplasty (THA) improves quality of life and increased demand is projected over the coming years 1. While lumbar plexus blocks (LPBs) reduce postoperative pain and opioid consumption after THA,2 3 risks include the potential for quadriceps weakness, bleeding, and neuraxial local anesthetic spread.…”
Section: Introductionmentioning
confidence: 99%
“…If the operation time is too long, it is difficult to meet the requirements. In addition, postoperative headache may occur during spinal anesthesia, which is the most painful problem for patients after spinal anesthesia, making anesthesiologists and surgeons worried about spinal anesthesia [ 3 , 4 ]. Epidural anesthesia has the advantages of less interference to the respiratory and circulatory system, less physiological impact, faster postoperative recovery, less complications, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) is a highly effective procedure for patients who have end-stage degenerative joint disease of the hip. [ 1 , 2 ] It was reported that over 300,000 THAs are being performed each year in the USA. [ 3 ] It is likely that the burden of inadequate postsurgical pain management associated with these procedures will also escalate.…”
Section: Introductionmentioning
confidence: 99%